Methyl N′-[(E)-1-phenylethylidene]hydrazinecarboxylate - Cheng, Xiang-Wei (International Union of Crystallography, 2008)
The molecule of the title compound, C(10)H(12)N(2)O(2), adopts a trans configuration with respect to the C=N bond. The dihedral angle between the phenyl ring and the hydrazine carboxylic acid mean plane is 25.23 (9)°. In the crystal structure, molecules are linked into chains by N—H⋯O hydrogen bonds and C—H⋯π interactions.